Hubungan Manajemen Waktu Belajar dan Hasil Belajar Peserta Didik Kelas V SDN 104256 Rugemuk - Siti Fatimah; Doddy Feliks P. Ambarita; Irsan Irsan; Wildansyah Lubis; Septian Prawijaya (Pusat Riset dan Inovasi Nasional, 2025)
This study was conducted with the aim of determining the relationship between time management and the learning outcomes of grade V students of SDN 104256 Rugemuk in the Social Studies subject